2016
DOI: 10.1038/srep21597
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of methods for the fusion transcripts detection from RNA-Seq data

Abstract: RNA-Seq made possible the global identification of fusion transcripts, i.e. “chimeric RNAs”. Even though various software packages have been developed to serve this purpose, they behave differently in different datasets provided by different developers. It is important for both users, and developers to have an unbiased assessment of the performance of existing fusion detection tools. Toward this goal, we compared the performance of 12 well-known fusion detection software packages. We evaluated the sensitivity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
132
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(136 citation statements)
references
References 45 publications
2
132
2
Order By: Relevance
“…The CGC is well suited to addressing such a problem, because multiple algorithms and datasets are easily available and thus each gene fusion caller can be rapidly and directly benchmarked against others. For this example, we will demonstrate how to compare the fusion callers EricScript, FusionCatcher, and STAR-Fusion on the CGC, based on the example in (Kumar, Vo, Qin, & Li, 2016). …”
Section: Basic Protocol 3: Interactive Analysis Of Results Using Datamentioning
confidence: 99%
“…The CGC is well suited to addressing such a problem, because multiple algorithms and datasets are easily available and thus each gene fusion caller can be rapidly and directly benchmarked against others. For this example, we will demonstrate how to compare the fusion callers EricScript, FusionCatcher, and STAR-Fusion on the CGC, based on the example in (Kumar, Vo, Qin, & Li, 2016). …”
Section: Basic Protocol 3: Interactive Analysis Of Results Using Datamentioning
confidence: 99%
“…In addition to being relatively less expensive with a quick turnaround time, it can also quantify expression levels and facilitate the detection of multiple fusion variants generated during the fusion event, making this a more ideal technology for gene fusion detection. However, RNA -seq routinely generates a daunting quantity of chimeric sequences, most of which are artifactual fusion sequences as a result of library artifacts and mapping errors [21,22], transcription-induced chimeras (TIC) resulting from intergenic splicing of adjacent genes, or passenger gene fusions. Bioinformatics methods that use stringent parameters to filter out artifactual chimeras may become less sensitive in detecting authentic fusions or underestimate their incidence, while filtering out the chimeras from adjacent genes will dismiss the close-range gene translocations.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still opportunity for performance improvement. Kumar et al [14] have shown that when comparing 12 different software packages they observed performance dependency in quality, read lengths, and supporting reads. More recently, Haas et al [15] have compared 16 different packages to assess fusion prediction.…”
Section: Introductionmentioning
confidence: 99%